2000
DOI: 10.3109/07357900009012204
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphoprotein Op18/Stathmin is Differentially Expressed in Ovarian Cancer

Abstract: To identify potential prognostic indicators of ovarian cancer and identify targets for therapeutic strategies, mRNA differential display was used to analyze gene expression differences in normal, benign, and cancerous ovarian tissue. One cDNA isolated by this technique, Op18/stathmin, is a highly conserved gene that is reported to have many different functions within a cell, including signal transduction, control of the cell cycle, and the regulation of microtubules. Quantitative Northern blot analysis of 12 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 20 publications
4
69
1
Order By: Relevance
“…This is the first report to provide a possible biophysical explanation for the increased sensitivity to Vinca alkaloids in cells over-expressing stathmin [12]. This mechanism could contribute to Vinca alkaloid selectivity for tumor cells in which stathmin is over-expressed compared to normal cells [7][8][9][10].…”
Section: Biological Significancementioning
confidence: 85%
See 1 more Smart Citation
“…This is the first report to provide a possible biophysical explanation for the increased sensitivity to Vinca alkaloids in cells over-expressing stathmin [12]. This mechanism could contribute to Vinca alkaloid selectivity for tumor cells in which stathmin is over-expressed compared to normal cells [7][8][9][10].…”
Section: Biological Significancementioning
confidence: 85%
“…A number of reports have shown that stathmin is expressed at high levels in a wide variety of human cancers [7][8][9][10]. Furthermore, it has been observed that stathmin modifies the antimitotic efficiency of antitumor cancer drugs, such as vinblastine (VLB) [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…54,55 Stathmin is expressed at high levels in a wide variety of human malignancies. [56][57][58][59] We identified overexpression of stathmin in ACC tissue. Further, we detected stathmin protein expression in 2 cases with NSG, 10 cases of PA and 10 cases of ACC using immunohistochemistry (Fig.…”
Section: Figurementioning
confidence: 99%
“…Poorly differentiated prostate tumor epithelial cells express more stathmin than do differentiated cells (Friedrich et al, 1995). Differentiation-stage-dependent expression of stathmin has also been noted in ovarian cancer (Price et al, 2000).…”
Section: Introductionmentioning
confidence: 92%
“…A gradient of active stathmin levels is necessary, since a balance of MT stabilizing and destabilizing factors are essential for maintenance of cellular functions. Stathmin has been found to be overexpressed in highly proliferative breast cancers and in ovarian cancers, particularly those that are platinum drug-resistant (Bieche et al, 1998;Brattsand, 2000;Curmi et al, 2000;Johnsson et al, 2000;Price et al, 2000). Overexpression of stathmin is also associated with the sensitivity to MT-binding anticancer agents (Alli et al, 2002).…”
Section: Introductionmentioning
confidence: 99%